Old wine in new skins? China’s neighbourhood transformation from danwei to shequ - Feng, Gequn; Chen, Fang (DIE ERDE – Journal of the Geographical Society of Berlin, 2019)
In this paper we argue that the urban neighborhood is a social product that serves as an instrument to ensure the social stability. Since the founding of the People’s Republic of China in 1949, the socialist work unit (danwei), which assumed a basic role in socialist policy and the embodiment of the institution, has been the elementary social cell in the planned economy. With the decline of danwei and the introduction of shequ in the market-oriented economy, neighbourhood transformation exercises a deep influence on social integration and personal unfolding and poses a big challenge for social coherence. After exploring the neighbourhood concepts in the Chinese context, the paper tracks the trajectory of neighbourhood transformation from danwei to shequ and analyses the practice of neighbourhood management. It concludes that the new practice of neighbourhood management remains a sort of ‘old wine in new skins’ in regard of its top-down approach.